Next-generation dendritic cell-based vaccines for leukemia patients - Hoffmann, Jean-Marc; Schmitt, Michael; Ni, Ming; Schmitt, Anita (Immunotherapy, 2017)
Up to today treatment of leukemia patients remains challenging and different therapies have been developed, among them the generation of dendritic cell (DC) vaccines. DCs, highly specific for immunogenic cancer antigens, are generated either ex vivo or in vivo and boost the immune response against leukemic cells. Nevertheless, response rates are still heterogeneous and DC vaccines need improvement. New methods for generating DC vaccines have been summed up under the term ‘next-generation DC vaccines’. They range from the analysis of human leukocyte antigen-ligandomes to immunogenic cell death inducers, from the production of viral vectors to mRNA transfection and finally from delivering peptides to DCs in vivo through either antibodies or cell-penetrating peptides. This review gives an overview of the latest developments in this still evolving field.
Published online 27 January 2017
Gesehen am 21.06.2018